Sons of fortune - Archer, Jeffrey, 1940-; Michael, Paul. (New York, NY : Audio Renaissance : Distributed by Holtzbrinck Publishers, LLC, 2002)
In Hartford, Connecticut, in the late 1940s, twin brothers are accidentally separated at birth. One brother grows up to be a war hero in Vietnam and a successful 1990s bank executive, while the other distinguishes himself as a lawyer and politician. When both men decide to run for governor, they learn the truth about their kinship-- and must face its tragic consequences.
Paul Michael, reader.
Abridged.
In container (16 cm.).
"This program is produced for mature audiences."
Keywords: Twins -- Fiction; Brothers -- Fiction; Hartford (Conn.) -- Fiction; Infants switched at birth -- Fiction; Vietnam War, 1961-1975 -- Veterans -- Fiction; Banks and banking -- Fiction; Politicians -- Fiction